1979
DOI: 10.2172/5858546
|View full text |Cite
|
Sign up to set email alerts
|

Creep behavior of bedded salt from southeastern New Mexico at elevated temperature

Abstract: Nos. 02-8B58and 05-7466). 1.The collected data included axial and lateral strain, axial and confinement stresses, time and temperature. Periodically, axial stress was adjusted to account for specimen strain in order to maintain a constant differential stress. Frequency of the stress correction was dependent on the rate of deformation; two or more corrections in a 24 hour period were typical. Data were automatically recorded with a printer, manually receded from the print-out to punched cards and reduced by mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
2

Year Published

1981
1981
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 0 publications
1
21
0
2
Order By: Relevance
“…Laboratory testing of salt cores has also provided significant insight into DRZ development. Hansen and Mellegard (1979) found that dilatancy is favored by conditions of low-confining stress and high deviatoric stress which characterize the region near an excavation. Laboratory testing has shown that a halite DRZ is self-healing given the proper stress conditions (Brodsky, 1990).…”
Section: Parameter Sourcesmentioning
confidence: 97%
“…Laboratory testing of salt cores has also provided significant insight into DRZ development. Hansen and Mellegard (1979) found that dilatancy is favored by conditions of low-confining stress and high deviatoric stress which characterize the region near an excavation. Laboratory testing has shown that a halite DRZ is self-healing given the proper stress conditions (Brodsky, 1990).…”
Section: Parameter Sourcesmentioning
confidence: 97%
“…Extensive research has been conducted in the laboratory to determine both the deformational and hydrological behavior of natural salt. Early work focused on the characterization of the elastic and inelastic viscoplastic flow properties of salt (e.g., Hansen and Mellegard 1977, Wawersik and Hannum 1979, Hansen and Mellegard 1980, Senseny 1986, Mellegard and Pfeifle 1993. Most of the early studies provided parameters for the constant-volume creep model, which was validated against large-scale thermal-mechanical experiments.…”
Section: Laboratory Studies Of Salt Damagementioning
confidence: 99%
“…Quasi-static properties were generated over a range of l o a d i n g rates frm d/dt -0,) of 150 t o 215 psi/min (RE/SPEC Inc. data, Gnirk e t al., 1973, Hansen andMellegard, 1977) to l o a d i n g rates of 30 to 60 psi/min (Sandia data, Wawersik, 1977, 1 9 7 8~) . The 30 psi/min loading rate was chosen to match t h a t of published data (Dreyer, 1972, Menzel andSchreiner, 1977).…”
Section: Thementioning
confidence: 99%
“…Tests d u r a t i o n s vary between 0.5 and 500 hours (Hanson, 1977, andHanson andMellegard, 1977). I n i t i a l efforts served to e v a l u a t e t h e s i g n i f i c a n c e of t r a n s i e n t creep on t h e p o s s i b l e r e p o s i t o r y c o n d i t i o n s , t o e s t a b l i s h upper (conservative) bounds for s t e a d y state creep rates a t r e l a t i v e l y low d e v i a t o r stress and temperature, and to test t h e a p p l i c a b i l i t y of a p i l l a r creep formula w h i c h has been widely used (Bradshaw and McClain, 1971) :…”
Section: -20mentioning
confidence: 99%
See 1 more Smart Citation